People´s right to tourism in Argentina. An approach from the perspective of social justice (Revista LIDER, 2020)
The significant path presented by Argentina in relation to the right to paid holidays, reaffirms itself from the new National Tourism Act, which states that it is a social and economic right of the people. However, reality makes it clear that most argentines remain excluded from tourism practices, especially those from disadvantaged social positions. What follows is an analysis of the level of access to tourist and recreational practices in Argentina, according to socioeconomic variables. At the same time it addresses the social tourism programs offered by the Ministry of Tourism of the Nation, from a conceptualization of social justice.